Trace Elements in Pineapple Jam from India - Mehta, B.H.; Rane, R.A. (Asian Journal of Chemistry, 2010)
Pineapple jams of different brands were analysed for Fe, Cu, Zn, Sn, Pb, Cr and Cd content by atomic absorption spectropho tometer (AAS). The physico-chemical characteristics such as pH, loss on drying, ash, degree brix, refractive index and acidity calculated as citric acid were also determined in all brands. On the basis of experimental data, fitnes's of the pineapple jam for consumption is recommended.